2015
DOI: 10.2514/1.c032583
|View full text |Cite
|
Sign up to set email alerts
|

Boundary-Layer Stability Analysis of the Mean Flows Obtained Using Unstructured Grids

Abstract: Boundary-layer stability analyses of mean flows extracted from unstructured-grid NavierStokes solutions have been performed. A procedure has been developed to extract mean flow profiles from the FUN3D unstructured-grid solutions. Extensive code-to-code validations have been performed by comparing the extracted mean flows as well as the corresponding stability characteristics to the predictions based on structured-grid solutions.Comparisons are made on a range of problems from a simple flat plate to a full airc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
4
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 20 publications
1
4
0
Order By: Relevance
“…Any concerns that may have existed about the suction-side T-S for this simulation due to the increased Reynolds number were relieved by results that showed that T-S was still sufficiently suppressed. All of these results agree reasonably well with follow-on work given by [23,24]. The latter paper included nonlinear PSE and secondary instability analyses that suggest DREs could indeed delay transition to turbulence by suppressing the most unstable crossflow disturbances.…”
Section: B Linear Stability Theory Calculationssupporting
confidence: 83%
“…Any concerns that may have existed about the suction-side T-S for this simulation due to the increased Reynolds number were relieved by results that showed that T-S was still sufficiently suppressed. All of these results agree reasonably well with follow-on work given by [23,24]. The latter paper included nonlinear PSE and secondary instability analyses that suggest DREs could indeed delay transition to turbulence by suppressing the most unstable crossflow disturbances.…”
Section: B Linear Stability Theory Calculationssupporting
confidence: 83%
“…The resulting glove midspan chord Reynolds number is 24.2 × 10 6 ; however, for convenience, it is identified as 24 × 10 6 elsewhere in the paper. In [29], both structured-grid (OVERFLOW, [31]) and unstructured-grid (FUN3D ¶ ) Navier-Stokes codes were used to compute the aircraft flowfield including the wing glove. Figure 2 shows the upper-surface C p distribution in the glove region.…”
Section: Computational Test Articlementioning
confidence: 99%
“…It should be noted that the isobars in the glove region have sweep angles smaller than the constant X∕C lines, particularly at larger distances from the leading edge. This unsweeping of the isobars has an important effect on boundary-layer stability, as discussed in [29] and summarized as follows. Figure 3 shows the C p distribution along the Y 234 in: butt line.…”
Section: Computational Test Articlementioning
confidence: 99%
See 1 more Smart Citation
“…Thus, the REBL permits a thorough analysis of separated flow systems, which is particularly relevant to the following study because sufficiently deep gaps may form localized pockets of separation. A full description of the extraction procedure is given in the work of Thomas et al [23], whereas similar methods have been developed by Malik [46] and Liao et al [47] for investigating the flow over a flat plate and aircraft configurations.…”
Section: A Base Flow 1 Boundary-layer Extractionmentioning
confidence: 99%